The effects of physical fitness on postactivation potentiation in professional soccer athletes - Guerra Jr, M. A.; Caldas, L. C.; Souza, H. L.; Tallis, J.; Duncan, M. J.; Guimarães-Ferreira, L. (The Journal of Strength and Conditioning Research, 2022)
To investigate the relationship of the response to postactivation potentiation (PAP) with scores of physical fitness. Twenty-four professional male soccer players undertook tests of agility, muscular power, aerobic capacity, and body composition. Conditioning activities (CAs) were performed consisting of plyometrics exercises and sprints with sled towing. In the first and second sessions, body composition, agility, power, and aerobic capacity were assessed. At the third session, countermovement jumps (CMJ) were performed with 1, 3, and 5 minutes after the execution of the CA. Significant differences were found for CMJ height 1, 3, and 5 minutes after the CA compared with baseline values (3.58, 5.10, 5.48%, respectively). There was a significant positive correlation between the level of general physical fitness and PAP (CMJ height increase) 5 minutes after (r = 0.73). When the athletes were divided into groups with higher and lower physical fitness, the CA caused a significant increase in CMJ height in both groups, but a significant difference (p < 0.05) was observed at all times after PAP induction, with better performance in higher versus lower fitness level. The results suggest that plyometrics exercises associated with sled towing sprints as a CA result in an increase in CMJ performance in athletes and that physical fitness directly influences the PAP occurrence, with higher fit players demonstrating an enhanced PAP response.